2003
DOI: 10.1002/bdrb.10039
|View full text |Cite
|
Sign up to set email alerts
|

Embryo/fetal development studies with hydroxypropyl methylcellulose acetate succinate (HPMCAS) in rats and rabbits

Abstract: The conclusion of the earlier study indicating that treatment with HPMCAS at doses up to and including 2500 mg/kg did not produce developmental toxicity was confirmed with these studies. It is likely that the clubfoot noted in the earlier rat teratology study was a misdiagnosis or artifact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Based on the scores, the low‐ and mid‐dose groups are comparable to the control group, and the high‐dose has ninefold more teratogenic severity than the control. An interesting point to note is the low score for this control group of SD rats (i.e., 5) compared to the above‐mentioned control/vehicle studies (mean score of 11 and 27 in Cappon et al., and Enright et al., , respectively). Again these differences in control group values are likely attributed to different conducting laboratories.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Based on the scores, the low‐ and mid‐dose groups are comparable to the control group, and the high‐dose has ninefold more teratogenic severity than the control. An interesting point to note is the low score for this control group of SD rats (i.e., 5) compared to the above‐mentioned control/vehicle studies (mean score of 11 and 27 in Cappon et al., and Enright et al., , respectively). Again these differences in control group values are likely attributed to different conducting laboratories.…”
Section: Resultsmentioning
confidence: 76%
“…The studies of Cappon et al. () and Enright et al. () provide vehicle‐treated groups of SD and New Zealand White (NZW) animals for calculation of teratogenic severity scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of fetal specimens has historically been plagued by regional and interlaboratory differences in terminology and criteria for recording findings that deviate sufficiently from normal (Black & Marks, 1986; Schardein, 1988) that can result in incorrect interpretation, unnecessary replication of studies, and difficulty in comparing results across laboratories (Cappon et al, 2003; Christian, 1993). Multiple international efforts toward establishing harmonized terminology resulted in the 2009 publication Terminology of Developmental Abnormalities in Common Laboratory Animals ( Version 2 ) (Makris et al, 2009) which is generally considered the gold‐standard reference for terminology of fetal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Oral gavage studies with Hydroxypropyl Methylcellulose acetate succinate in rats and rabbits at doses up to 2,500 mg/kg/day indicated no treatment‐related effects on fertility or embryo–fetal development (Hoshi et al, 1985a, b; Cappon et al, 2003). Similarly, oral gavage studies with PS 80 in rats at doses up to 5,000 mg/kg indicated no effects on embryo–fetal development (NTP, 1992).…”
Section: Introductionmentioning
confidence: 99%